Social interaction and cultural adjustment of International and Malaysian students at UPSI - Nor Ili Ahmad Tajuddin (2022)
The purpose of this study is to explore the social interactions among International and Malaysian students at Universiti Pendidikan Sultan Idris (UPSI) Tanjung Malim, Perak. The study's goal was i) to understand the challenges faced by international and Malaysian students during their social interactions. ii) to describe how international and Malaysian students cope with the challenges during social interaction, iii) to explore international and Malaysian students expectations of UPSI programs in promoting social interaction between them. This study uses a qualitative method with a case study approach and the data were obtained through the interview (11 participants), observation, and document analysis. The data were subsequently analyzed using manual methods. To ensure validity and reliability, data triangulation was used. The findings revealed (objective-1) that the language barrier, lack of social skills, personality traits, lack of confidence, and accents are the most common challenges faced by International and Malaysian students in UPSI during their social interaction. They solve the problem (objective-2) by coping with internal emotions, using body language, asking for clarification, engaging in social activities, lowering the ego, starting a conversation, and building self-confidence. They expected (objective-3) the UPSI in the future to create such a program that can build a conversation between International and Malaysian students and be mandatory for participation. The study's findings are expected to assist university policymakers in encouraging programs that promote social interaction between International and Malaysian students.